El debido proceso como derecho constitucional y su vulneración en los casos de violencia intrafamiliar - Vélez Mora, Verónica del Pilar (2013)
The present thesis, whose theme is "The due process as a constitutional right and its violation in cases of domestic violence", consists of six chapters which are detailed in the research topic concepts. In the introduction, it is a summary of the application of due process in cases of domestic violence, on the critical, reality focuses on the implementation of protective measures without observing the rules of due process, states the overall objectives and specific hypotheses, independent and dependent variables and resources are detailed. In the theoretical framework, consisting of background research, rationale: Doctrine, Jurisprudence, Legislation and Comparative Law is based, from the object of study, which refers to different laws especially the constitution of the Republic and its applicability due process. In the methodology , determine the methods , the techniques applied in the field , the application of surveys to citizens of Canton Quevedo, a lawyer and the interview was conducted with such results tabulation, analysis and processing data, prepared the report of the investigation and testing of the hypothesis. It made the findings and recommendations and the proposed legal reform to art. 13 of the Law on Violence Against Women and Family